(untitled) (International Journal of Engineering and Computer Science, 2014)
In this Paper we are implementing Prototype solar PV monitoring and optimization includes a data acquisition system, Supervisory monitoring and control station at plant level and Decision Support System (DSS) at the Central Control Station. This Prototype System consist two plant level monitoring (PLM) systems and Central Control Station (CCS). One of Plant level system is for basic data acquisition from weather sensors related to sun energy and Sting Monitoring Units. Another plant level system will have features along with the solar tracker system. The CCS continuous on-line monitoring, control, storage, and reporting at plant level and collects data from PLM’s via wireless module with time stamp for real time processing, storage, alarming, reporting and displaying. This system designed monitoring and analytics system.